2023
DOI: 10.1007/s00018-023-04928-z
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ signaling links early life endocrine-disrupting chemicals exposure to suppression of nucleotide excision repair in rat myometrial stem cells

Maria Victoria Bariani,
Yan-Hong Cui,
Mohamed Ali
et al.

Abstract: Environmental exposure to endocrine-disrupting chemicals (EDCs) is linked to the development of uterine fibroids (UFs) in women. UFs, non-cancerous tumors, are thought to originate from abnormal myometrial stem cells (MMSCs). Defective DNA repair capacity may contribute to the emergence of mutations that promote tumor growth. The multifunctional cytokine TGFβ1 is associated with UF progression and DNA damage repair pathways. To investigate the impact of EDC exposure on TGFβ1 and nucleotide excision repair (NER… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Therefore, we incorporated the unique biology of reprogrammed MMSCs into our understanding of UF pathogenesis linked to EDC exposure. Notably, our previous and recent studies also demonstrated that single EDC exposure can increase the number of MMSCs, 9 decrease the DNA repair capacity, 1012 and activate the pro-inflammatory pathway, 13 indicating that developmental EDC exposure altered the MMSC characteristics in an orchestrated manner (Figure 2).…”
mentioning
confidence: 79%
“…Therefore, we incorporated the unique biology of reprogrammed MMSCs into our understanding of UF pathogenesis linked to EDC exposure. Notably, our previous and recent studies also demonstrated that single EDC exposure can increase the number of MMSCs, 9 decrease the DNA repair capacity, 1012 and activate the pro-inflammatory pathway, 13 indicating that developmental EDC exposure altered the MMSC characteristics in an orchestrated manner (Figure 2).…”
mentioning
confidence: 79%
“…Female Eker rats exposed to DES 11μg/d on days 10, 11, and 12 after birth reprogramed the methylome and found an augmenting estrogen activity of myometrial stem cells, leading to a “hyper-inflammatory phenotype” and an increased hormone-dependent risk of UFs ( 45 , 46 ). Further investigation into the molecular mechanisms implicated that early life exposure to DES suppressed nucleotide excision repair in rat myometrial stem cells through TGF-β signaling ( 47 ). Moreover, studies demonstrated that Vitamin D3 could mitigate the DNA damage caused by developmental DES exposure in uterine myometrial stem cells, effectively reducing the incidence of UF development ( 48 ).…”
Section: Introductionmentioning
confidence: 99%